Characterization of the humoral and cellular immunity induced by a recombinant BCG vaccine for the respiratory syncytial virus in healthy adults - Pacheco, Gaspar A.; Andrade, Catalina A.; Gálvez, Nicolás M.S.; Vázquez, Yaneisi; Rodríguez-Guilarte, Linmar; Abarca, Katia; González, Pablo A.; Bueno, Susan M.; Kalergis, Alexis M. (Frontiers in Immunology, 2023)
Introduction The human respiratory syncytial virus (hRSV) is responsible for most respiratory tract infections in infants. Even though currently there are no approved hRSV vaccines for newborns or infants, several candidates are being developed. rBCG-N-hRSV is a vaccine candidate previously shown to be safe in a phase I clinical trial in adults (clinicaltrials.gov identifier #NCT03213405). Here, secondary immunogenicity analyses were performed on these samples. Methods PBMCs isolated from immunized volunteers were stimulated with hRSV or mycobacterial antigens to evaluate cytokines and cytotoxic T cell-derived molecules and the expansion of memory T cell subsets. Complement C1q binding and IgG subclass composition of serum antibodies were assessed. Results Compared to levels detected prior to vaccination, perforin-, granzyme B-, and IFN-γ-producing PBMCs responding to stimulus increased after immunization, along with their effector memory response. N-hRSV- and mycobacterial-specific antibodies from rBCG-N-hRSV-immunized subjects bound C1q. Conclusion Immunization with rBCG-N-hRSV induces cellular and humoral immune responses, supporting that rBCG-N-hRSV is immunogenic and safe in healthy individuals. Clinical trial registration https://classic.clinicaltrials.gov/ct2/show/, identifier NCT03213405.